Barriers to recruitment for surgical trials in head and neck oncology: a survey of trial investigators. Issue 4 (11th April 2013) - Kaur, Geetinder; Hutchison, Iain; Mehanna, Hisham; Williamson, Paula; Shaw, Richard; Tudur Smith, Catrin
Abstract : Objectives: Many randomised trials in surgery suffer from recruitment rates that lag behind projected targets. We aim to identify perceived barriers to recruitment among these pioneering trials in the field of head and neck cancer surgery. Design: Recruiting centres to all three trials (Selective Elective Neck Dissection (SEND), Positron Emission Tomography (PET)-Neck and Hyperbaric Oxygen in the Prevention of Osteoradionecrosis (HOPON)) were contacted by email by the chief investigators. Responders were asked to complete a web-based survey in order to identify the barriers to recruitment in their centre and grade each by severity. Setting: Secondary care: 44 head and neck oncology regional referral centres. Participants: Analysis was based on 85 responses evenly distributed between the three trials. Results: The most commonly identified perceived barriers to recruitment (more than 50% of responders identified the item as a barrier in all the three trials) in the order of frequency were: patients consent refusal because of expressed treatment preference, patients consent refusal owing to aversion to randomisation, excess complexity/amount of information provided to patients and lack of time in clinic to accommodate research. The most severely rated of these problems was consent refusal because of the expressed treatment preference and lack of time in the clinic. Conclusions: Our findings confirm others' work in surgery that the most significant barrier to trial recruitment in head and neck cancer surgery is the patient's preference for one arm of the trial. It may be that additional training for those taking consent may be helpful in this regard. It is also important to adequately resource busy surgical clinics to support clinical trial recruitment.